No Dose Adjustment is Recommended for Digoxin, Warfarin, Atorvastatin or a Combination Oral Contraceptive When Coadministered with Dulaglutide - de la Peña, Amparo; Cui, Xuewei; Geiser, Jeanne; Loghin, Corina (Clinical pharmacokinetics, 2017)
Background Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) for the treatment of type 2 diabetes mellitus are known to delay gastric emptying (GE). The potential effect of the GLP-1 RA dulaglutide on the pharmacokinetics (PK) of four orally administered drugs and on the pharmacodynamic (PD) effect of warfarin was investigated. Methods In four separate clinical pharmacology studies, digoxin, warfarin, atorvastatin and Ortho-Cyclen ® were orally administered to healthy subjects with and without a subcutaneous dose of dulaglutide 1.5 mg. The effect of dulaglutide coadministration was assessed based on the PK parameters of key analytes. For warfarin PD, the effect of dulaglutide on the international normalized ratio (INR) was evaluated. Results Areas under the concentration–time curves (AUCs) with and without dulaglutide were similar for all analytes except atorvastatin, where it was reduced by 21%. Maximum concentrations ( C max ) were generally lower following coadministration with dulaglutide, with statistically significant reductions (90% confidence intervals of geometric least squares means ratios outside 0.80–1.25) for all analytes except R-warfarin. For all analytes, there was a general trend for the time to C max ( t max ) to increase following coadministration with dulaglutide. For warfarin, dulaglutide coadministration had no statistically significant effect on the maximum INR (INR max ); however, a 2% increase in area under the INR curve (AUC INR ) was observed. Conclusions Dulaglutide did not affect the absorption of the tested medications to a clinically relevant degree. Based on the PK and PD evaluations, no dose adjustments for digoxin, warfarin, atorvastatin and Ortho-Cyclen ® are recommended when coadministered with dulaglutide. Clinical trial registration numbers NCT01458210, NCT01436201, NCT01432938, and NCT01250834.